2018
DOI: 10.18805/ijar.b-387
|View full text |Cite
|
Sign up to set email alerts
|

Studying the antioxidant role of mushroom against hazards of gamma radiation exposure in male rats

Abstract: This study aimed to investigate the antioxidant role of dried mushroom (DM) against hazards of gamma-irradiation in male rats. In this study, exposure of rats to whole body g-radiation (6 Gy) resulted in hepatic oxidative stress (a significant increase in lipid peroxidation concomitant with a significant decrease in glutathione content and antioxidant enzyme activities); increase liver function enzymes and histopathological disorders. Treatment of irradiated rats with 10% DM significantly improved radiation-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The antioxidant activity of the group treated with 10% dried mushrooms was significantly increased in comparison to the irradiated group. According to these results, the authors suggest that oyster mushroom can improve the antioxidant status and minimize the radiation-induced injury (Hamza et al, 2018).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The antioxidant activity of the group treated with 10% dried mushrooms was significantly increased in comparison to the irradiated group. According to these results, the authors suggest that oyster mushroom can improve the antioxidant status and minimize the radiation-induced injury (Hamza et al, 2018).…”
Section: Resultsmentioning
confidence: 93%
“…They stated that antioxidant enzyme activity of radioresistant rat increased significantly and although there was no significant difference between radioresistant and radiosensitive group in terms of MDA level, lipid peroxidation increased according to radiation dose in both groups (Hardmeier et al, 1997). Hamza et al (2018). gave rats dried oyster mushroom before whole body γ radiation (6 Gy).…”
Section: Resultsmentioning
confidence: 99%
“…As we all know, oxidative injury may contribute to the final pathway of organ dysfunction. It is accepted that the production of oxygen-derived radical species constitutes one of the major events involved in the initiation, maintenance and reversibility of functional alterations associated with ischemia-reperfusion injury Raedschelders et al, (2012) and Ilhan et al, (2019) and Hamza et al, (2019). The activation of enzymes such as xanthine oxidase or the uncoupling of the mitochondrial electron transport chain are believed to play an important role in the production of reactive oxygen species during reperfusion Peglow et al, (2011).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was found that lentinan sulfate polysaccharide can improve the multiple organ dysfunction syndrome induced by yeast polysaccharides in mice and reduce the vacuolization of mouse liver 46]. The improvement in liver morphology can be attributed to the bioactive compounds in mushrooms such as B vitamins, minerals, polysaccharides, lentinan and so on, which have the effect of liver protection and enhancing the antioxidant capacity of the liver [43,[46][47][48][49][50][51][52][53][54]. The present study showed that LEF can reduce hepatic MDA levels and enhance the ability of hepatocytes to remove hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%